Exploring the prevalence and management of wounds for people with dementia in long‐term care. Issue 3 (14th February 2020) - Parker, Christina N.; Finlayson, Kathleen J.; Edwards, Helen E.; MacAndrew, Margaret
Abstract: The prevalence of wounds and comorbidities such as dementia increase with age. With an ageing population, the likelihood of overlap of these conditions is strong. This study aimed to determine the prevalence of wound types and current management strategies of wound care for people with dementia in long‐term care (LTC). A scoping literature review, a cross‐sectional observational and chart audit study of residents in dementia specific facilities in LTC were conducted. The scoping review indicated that people with dementia/cognitive impairment are often excluded from wound related studies andof the nine studies included in this review, none looked at the prevalence of types of wounds other then pressure injuries. In the skin audit, skin tears were noted as the most common wound type with some evidence‐based practice strategies in place for residents. However, documentation of current wound occurred in less than a third of residents with wounds. This is the first study to note the prevalence of different wound types in people with dementia and current management strategies being used across two dementia‐specific facilities and a lack of research in this area limits evidence in guiding practice.